Dekonstruksi Konsep Ridho Antar Umat Beragama dalam QS. al-Baqarah 120 Menggunakan Pendekatan Ma’na Cum Maghza - Rinaldo, Rinaldo (Abdurrauf Science and Society, 2025)
Misogynistic allegations between religious communities in Islamic religious texts make the permanent doctrine of an inclusive understanding of Islam among its adherents make the confusion of Islam revealed as a blessing for the whole world. So in this study the author wants to present the deconstruction of the concept of inter-religious ridho in Qs. al-Baqarah : 120 comprehensive and compatible. This study uses the Ma'na Cum Magzha approach which was initiated by Sahiron Syamsudin with a descriptive-analytical-critical presentation method that adheres to the workings of deconstruction. The results of this study show that first, the main message of the Koran in this verse is that discontent is directed at the inherent nature of the Jews and Christians at the time of the Apostles, namely treason and full of bad tactics. Second, the concept of pleasure for a person no longer looks at what religion he is, but at what is his nature, character and behavior, so that the deconstruction of the concept of ridho provides a new perspective for understanding the Koran in order to avoid religious inclusivism. Abstrak: Dugaan misoginis antar umat beragama dalam teks-teks agama Islam membuat doktrin permanen terhadap pemahaman Islam inklusif pada penganutnya membuat kerancuan Islam diturunkan sebagai rahmat bagi seluruh alam. Maka dalam penelitian ini penulis ingin menghadirkan dekonstruksi konsep ridho antar umat beragama dalam Qs. al-Baqarah : 120 yang komprehensif dan kompatibel. Pada penelitian ini menggunakan pendekatan Ma’na Cum Magzha yang digagas oleh Sahiron Syamsudin dengan metode penyajian deskriptif-analitis-kritis yang menganut cara kerja dekonstruksi. Hasil penelitian ini menjunjukkan pertama,  pesan utama al-Quran dalam ayat ini adalah ketidakridhan itu tertuju terhadap sifat yang melekat pada orang Yahudi dan Nasrani pada zaman Rasul yaitu khianat dan penuh dengan siasat buruk. Kedua, konsep keridhoan terhadap seseorang tidak lagi melihat kepada agamanya apa, namun kepada apa yang menjadi sifat, watak dan perilakunya, sehingga dekonstruksi konsep ridho ini memberikan padangan baru untuk memahami al-Quran agar terhindari dari inklusivisme beragama. Kata kunci : Dekonstruksi, Ridho, Ma’na-Cum-Magzha.